2005
DOI: 10.1016/j.nbd.2005.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated amyloid deposition, neurofibrillary degeneration and neuronal loss in double mutant APP/tau transgenic mice

Abstract: Even though the idea that amyloid B peptide accumulation is the primary event in the pathogenesis of Alzheimer's disease has become the leading hypothesis, the causal link between aberrant amyloid precursor protein processing and tau alterations in this type of dementia remains controversial. We further investigated the role of B-amyloid production/deposition in tau pathology and neuronal cell death in the mouse brain by crossing Tg2576 and VLW lines expressing human mutant amyloid precursor protein and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
117
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 23 publications
5
117
2
1
Order By: Relevance
“…This lowered transgene expression served to highlight the power of incorporating the London mutation, and may also reflect an effect of mutant tau, consistent with a previous report that tau accelerated APP-related pathology. 37 Despite lower levels of human APP, plaque deposition was enhanced in rTg3696AB versus Tg2576 brain. In Tg2576, previous studies observed the first formation of A␤ plaques between 7 and 10 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lowered transgene expression served to highlight the power of incorporating the London mutation, and may also reflect an effect of mutant tau, consistent with a previous report that tau accelerated APP-related pathology. 37 Despite lower levels of human APP, plaque deposition was enhanced in rTg3696AB versus Tg2576 brain. In Tg2576, previous studies observed the first formation of A␤ plaques between 7 and 10 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…41 Other groups observed an increase in both A␤ deposition and NFT pathology in Tg2576 crossed with mice harboring three mutations in tau (VLW; G272V, P301L and R406W). 37 In this model, an increase in tau phosphorylation was hypothesized to reciprocate a link between the two pathological cascades. 42 Unfortunately, a clear demonstration of the molecular connection between A␤ plaques and NFTs remains enigmatic.…”
mentioning
confidence: 99%
“…An association between Aβ and hyperphosphorylated tau has been shown (Ribe et al, 2005;Oddo et al, 2003). Soluble Aβ can induce inactivation of phosphatases (Vogelsberg-Ragaglia et al, 2001) and activation of tau kinases (Hoshi et al, 2003;Otth et al, 2002), and promoting tau phosphorylation (Hoshi et al, 2003;Otth et al, 2002;Zheng et al, 2002) and the direct interaction between tau and Aβ induces tau aggregation and hyperphosphorylation (Rank et al, 2002).…”
Section: Interplay Between Dyrk1a Aβ and Taumentioning
confidence: 99%
“…We used the Morris water maze (MWM) test to evaluate the working and reference memory function in response to treatment with 4-PBA in Tg2576 mice, as previously described (Ribé et al, 2005). Groups of female Tg2576 mice treated with 4-PBA (n ¼ 8), or vehicle (n ¼ 8) and nontransgenic littermates (n ¼ 10) underwent spatial reference learning and memory testing in the MWM test at 16 months of age.…”
Section: Morris Water Maze Testmentioning
confidence: 99%